Accuracy-dependent dose-constraints and dose-based safety margins for organs-at-risk in radiotherapy - Joep C. Stroom; Sandra C. Vieira; Carlo Greco; Sebastiaan M.J.J.G. Nijsten (Physics and Imaging in Radiation Oncology)
Background and purpose: Geometrical uncertainties in radiotherapy are generally accounted for by margins for tumors, but their effect on organs-at-risk (OARs) is often ignored. We developed a model that incorporates dose- and geometry-based uncertainties in OAR planning using dose constraints. Materials and methods: Radiotherapy uncertainties cause real dose-volume histograms (DVHs) to spread around the planned DVH. With a published OAR dose constraint D(Vcrit) < Dcrit such that complication probability < Y%, real differences from planned Dcrit can be described by mean- (MDDcrit) and standard deviations (SDDcrit). Assuming complications are associated with the worst DVHs, New dose constraints that maintain complication probability can be derived for new treatments:Dcrit,New = Dcrit,publ + Φ−1(1 - Y%) * (SDDcrit,publ - SDDcrit,New) + (MDDcrit,publ - MDDcrit,New),with Φ−1(x) the inverse cumulative normal distribution function. Setting SDDcrit,New = MDDcrit,New = 0 in the recipe yields the “True” critical dose, and Dcrit,True - Dcrit,publ can be considered a dose-based safety margin (DSM).As hypothetical example, we estimated MDDcrit and SDDcrit values by simulating geometric errors in our clinical treatment plans and adding dose-based uncertainty. Over 1000 OARs with 108 different regular- and hypo-fractionation constraints were simulated. We assumed accuracy SDs to change from 2.5mm/3% to 1.5mm/2%. Results: Results varied per OAR, fractionation, and constraint-type. If our 2.5mm/3% MDDcrit and SDDcrit values approximated dose-constraint studies, on average the DSM would be 4.5 Gy (18%) and our dose constraints would increase with 1.2 Gy (5%). Conclusions: We introduced a first model relating dose constraints and complication probabilities with treatment uncertainties and safety margins for OARs. Among other things, it quantified how higher constraints can be applied with increasing radiotherapy accuracy.